Intestinal Morphologic and Microbiota Responses to Dietary Bacillus spp. in a Broiler Chicken Model - Li, Cheng-liang; Wang, Jing; Zhang, Hai-jun; Wu, Shu-geng; Hui, Qian-ru; Yang, Cheng-bo; Fang, Re-jun; Qi, Guang-hai (Frontiers in Physiology, 2019)
Dietary inclusion of probiotic Bacillus spp. beneficially affect the broiler chickens by balancing the properties of the indigenous microbiota causing better growth performance. The effects of three Bacillus spp. on the growth performance, intestinal morphology and the compositions of jejunal microflora were investigated in broiler chickens. A total of 480 1-day-old male Arbor Acres broilers were randomly divided into four groups. All groups had six replicates and 20 birds were included in each replicate. The control birds were fed with a corn-soybean basal diet, while three treatment diets were supplemented with Bacillus coagulans TBC169, B. subtilis PB6, and B. subtilis DSM32315 with a dosage of 1 × 109 cfu/kg, respectively. The experiment lasted for 42 days. The compositions and diversity of jejunal microflora were analyzed by MiSeq high-throughput sequencing. The B. coagulans TBC169 group showed marked improvements of growth performance, nutrient digestibility and intestinal morphology compared with the other B. subtilis treatments. B. coagulans TBC169 supplementation improved the average body weight (BW), average daily weight gain (ADG), total tract apparent digestibility of crude protein and gross energy (GE), and reduced feed conversion rate (FCR) compared with the control group (P < 0.05). The villus height to crypt depth ratio (VH/CD) of jejunum and duodenum was increased in the birds fed with B. coagulans TBC169 compared with the control group (P < 0.05). However, two B. subtilis treatments presented more positive variation of the jejunum microflora of chickens than that in the B. coagulans TBC169 group. B. subtilis PB6 and B. subtilis DSM32315 treatments improved the diversity of jejunal microbiota on day 21 compared with the control (P < 0.05), while which were decreased on day 42 (P < 0.05). The supplementation with B. coagulans TBC169 significantly improved the proportion of Firmicutes, otherwise two B. subtilis significantly improved the proportion of Proteobacteria, Bacteroidetes, Actinobacteria, and Acidobacteria at the phylum level during starter phase and decreased the proportion of Bacteroidetes during growing phase compared with the control. The supplementation with B.subtilis DSM32315 significantly improved the proportion of Clostridiales during starter phase, whereas two B. subtilis significantly improved the proportion of Pseudomonas, Burkholderia, Prevotella, DA101 during growing phase at the genus level compared with the control. In conclusion, the dietary supplementation with probiotic Bacillus spp. strains improved body weight and intestinal morphology in broiler chickens, which might be associated with the gut microbiota.